Strengthening the Inclusive Economy to Support the SDGs Through the Population Sector - Agil Nur, Faizal; Sulistyono, Setyo Wahyu (Program Studi Ekonomi Pembangunan Universitas Muhammadiyah Malang, 2024)
High economic growth not only helps improve welfare but is also an indicator of the success of a country's economic development. However, high economic growth cannot guarantee that everyone will get the same benefits. Therefore, this research aims to determine the role of the population sector in supporting the achievement of sustainable development goals (SDGs) in the context of strengthening an inclusive economy. This research uses secondary data from the World Bank and was carried out using multiple linear regression analysis techniques. The research results show that inflation, population, unemployment and per capita income significantly affect economic growth simultaneously. This study shows that Indonesia's inclusive economy still faces many challenges.